PEMANFAATAN KONDENSAT STEAM UNTUK HEATING AIR HANGAT PADA PLATE HEAT EXCHANGER DI PLANT PKO FRAKSINASI COCOA BUTTER SUBSTITUTE - Caniago, Mitha Fitriani; Youfa, Rita (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2021)
One of the companies operating in the palm oil processing industry uses steam as a heating medium in its process equipment. There is an energy-saving initiative in place that involves recovering steam condensate to heat warm water through a Plate Heat Exchanger (PHE) unit. The heat exchange in the PHE occurs in a counter-current manner with a target water temperature of 40°C (set point). The heating process is conducted in a circulation loop where the steam condensate enters the PHE to heat the warm water, and the output is then returned to the condensate storage tank before re-entering the PHE. This study analyzes the energy recovery process of the heat contained in the condensate for heating purposes. Based on observations, the steam condensate can raise the water temperature to the set point. However, using condensate for water heating takes longer compared to using steam. Additionally, in terms of quantity, a higher condensate flow rate is required compared to steam heating. Utilizing steam condensate as a heat source can reduce steam consumption, thereby lowering production costs at the PKO plant.